OKUL ÖNCESİ ÖĞRETMENLERİNİN SINIF YÖNETİM BECERİLERİ VE UYGULAMALARINA YÖNELİK GÖRÜŞLERİNİN İNCELENMESİ. - SADIK, Fatma; DİKİCİ SIĞIRTMAÇ, Ayperi (Electronic Turkish Studies)
This is a mixed method research study aiming to investigate the views of pre-school teachers about classroom management skills and practices. 145 teachers from 80 pre-school institutions located in the center of the province of Adana participated at the quantitative aspect of the research study while eight teachers got involved in the qualitative part on a voluntary basis. The quantitative data gained through the Classroom Management Skills Scale (CMSS) was analyzed using the ttest and ANOVA while the interview data was analyzed by using the content analysis technique. The results showed that the classroom management skills of pre-school teachers are on a high level. The views of teachers who graduated from open-universities or short-cycle programs and the views of teachers with more than 10 years of experience were found to be more positive. The availability of staff to assist in the classroom as well as inclusive practices created differences with regard to the teachers' classroom management skills. The teachers who experienced an organized and interesting learning environment stated that they have problems because of crowded classrooms. The teachers who usually employ pre-made-plans stated that they are flexible with regard to the practices. The classroom rules are established together with the students in the first week and conciliated through explanations, discussions and modifications. According to the results of the study, small working groups are formed in the class and out-of-classroom activities are practiced very rarely. The most common rewards used by the teachers are verbal praises and positive facial expressions while misbehaviors results in verbal interventions (warnings, reminding the rules) and punishment. The teachers who perceive themselves as more efficient in controlling their emotions and communication described their views about classroom management as non-interventionist and interactionalist.